Study and optimization of a microfluidic paper based analytical device for the quantification of salivary copper - Almeida, Adriana Raquel Gomes Tavares (2022)
Early diagnosis of pathology can promote a better recovery and treatment. Thus, the development the devices the rapid evaluation of the health condition, contribute to this process. In this context, in the recent years there has been growth in the development of low cost, easy to use devices. In this work, a microfluidic paper-based analytical device (μPAD) was development for the determination of copper in human saliva, being a form of rapid test. The device is suitable for the detection of excess copper, as consequently to change the healthy status. The development of the device involved several studies in order to get the rapid determination, accurate, cheaper and easy to use. Colorimetric reaction was chosen between copper and diphenylcarbazide create the complex of red colour. After the reaction time has elapsed, a scanner is used to obtain the digital image of μPAD detection zone, in order to calculate the absorbance based on the intensity of colour of each analytical local, obtained by Image J software. This device provides a copper determination in the range of 80.0 – 600 μg/L, a calibration curve of A= (0.0701±0.0008) [Cu2+] – (0.0043 ± 0.0004), the limit of detection of 17 μg/L and the limit of quantification of 56 μg/L. After inserting the sample in the μPAD, it can be digitized, within a time period of 20 - 40 min. The accuracy of the results was assessed by calculating recovery percentages using saliva from volunteers.